2018
DOI: 10.1155/2018/3276162
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Aldose Reductase, Protein Glycation, and Antioxidant Inhibitory Activities of Bioactive Flavonoids in Matricaria recutita L. and Their Structure-Activity Relationship

Abstract: The inhibitory activities of Matricaria recutita L. 70% methanol extract were evaluated by isolating and testing 10 of its compounds on rat lens aldose reductase (RLAR), advanced glycation end products (AGEs), and 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging. Among these compounds, apigenin-7-O-β-D-glucoside, luteolin-7-O-β-D-glucoside, apigenin-7-O-β-D-glucuronide, luteolin-7-O-β-D-glucuronide, 3,5-O-di-caffeoylquinic acid, apigenin, and luteolin showed potent inhibition, and their IC50 values in R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…It is supposed that CLE has synergy effect in combination luteolin, its glycoside and chlorogenic acid. Among flavonoids present in CLE, luteolin-7-O-β-D-glucuronide exhibited antioxidative and AGE-inhibitory activities [37]. Chlorogenic acid is well known to have anti-obesity and anti-diabetic effects [38].…”
Section: Discussionmentioning
confidence: 99%
“…It is supposed that CLE has synergy effect in combination luteolin, its glycoside and chlorogenic acid. Among flavonoids present in CLE, luteolin-7-O-β-D-glucuronide exhibited antioxidative and AGE-inhibitory activities [37]. Chlorogenic acid is well known to have anti-obesity and anti-diabetic effects [38].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the intracellular accumulation of a polar sugar alcohol can cause a hyperosmotic effect, resulting in a fluid infusion to counteract the osmotic gradient. Fluid influx has been demonstrated to cause alterations in membrane permeability and the start of cellular disease [ 42 , 43 ]. Rat lenses treated in 25 mM glucose for 6 days exhibited enhanced intracellular sorbitol accumulation.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the correlation could be interfered with by other mechanisms. For example, Sompong [14] and Hwang [17] found that there was no correlation between the percentage AGEs inhibition and radical scavenging activity, whereas Mutsuda [18] suggested that strong AGEs inhibition activity tended to exhibit strong radical scavenging activity.…”
Section: Resultsmentioning
confidence: 99%